2016
DOI: 10.1038/ncomms12756
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase D regulates positive selection of CD4+ thymocytes through phosphorylation of SHP-1

Abstract: Thymic selection shapes an appropriate T cell antigen receptor (TCR) repertoire during T cell development. Here, we show that a serine/threonine kinase, protein kinase D (PKD), is crucial for thymocyte positive selection. In T cell-specific PKD-deficient (PKD2/PKD3 double-deficient) mice, the generation of CD4 single positive thymocytes is abrogated. This defect is likely caused by attenuated TCR signalling during positive selection and incomplete CD4 lineage specification in PKD-deficient thymocytes; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…However, more recent work by Xiao et al [15], in which Shp1 mutants were expressed in mev hematopoietic stem cells, found that phosphorylation at Y564 was critical for the phosphatase activity of Shp1, whereas phosphorylation at Y536 was more important for binding signaling molecules, such as Grb2 or Stat5, and a Y536/564E double-mutant Shp1 shows enhanced phosphatase activity. Phosphorylation of S557 by PKD in T cells and phosphorylation of S591 by PKC have been proposed to negatively regulate Shp1 [26][27][28][29]. Other features of the C-terminal tail of Shp1 that could also impact regulation include a nuclear localization signal [30], a lipid raft localization signal, and protein-protein interaction domains, reviewed in Poole and Jones [31].…”
Section: Shp1 Structure and Regulationmentioning
confidence: 99%
“…However, more recent work by Xiao et al [15], in which Shp1 mutants were expressed in mev hematopoietic stem cells, found that phosphorylation at Y564 was critical for the phosphatase activity of Shp1, whereas phosphorylation at Y536 was more important for binding signaling molecules, such as Grb2 or Stat5, and a Y536/564E double-mutant Shp1 shows enhanced phosphatase activity. Phosphorylation of S557 by PKD in T cells and phosphorylation of S591 by PKC have been proposed to negatively regulate Shp1 [26][27][28][29]. Other features of the C-terminal tail of Shp1 that could also impact regulation include a nuclear localization signal [30], a lipid raft localization signal, and protein-protein interaction domains, reviewed in Poole and Jones [31].…”
Section: Shp1 Structure and Regulationmentioning
confidence: 99%
“…This study identified the phosphatase SHP1 ( Ptpn6 ) Ser557 residue as a PKD substrate. Remarkably, this study reported the generation of a “knockin” mouse bearing a phosphorylation-deficient SHP1 variant (S557A mutation), to demonstrate that SHP1-Ser557 phosphorylation is required for optimal T cell differentiation in the thymus ( 32 ).…”
Section: Tcr Signaling By Global Phosphoproteomicsmentioning
confidence: 99%
“…Studies have shown that PKD1 is not expressed in murine T-and B-lymphocytes, nor in malignant B cells, nor in thymus and spleen(94)(95)(96), PKD2 being the major PKD isoform expressed. However, ectopic expression of a constitutively active form of PKD1 induced pre-T-cell proliferation(97) illustrating again the proproliferative role of PKD1 when expressed and raising questions about its putative function in hematopoietic malignancies.…”
mentioning
confidence: 99%